2020
DOI: 10.1038/s12276-020-00504-8
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine reliance in cell metabolism

Abstract: As knowledge of cell metabolism has advanced, glutamine has been considered an important amino acid that supplies carbon and nitrogen to fuel biosynthesis. A recent study provided a new perspective on mitochondrial glutamine metabolism, offering mechanistic insights into metabolic adaptation during tumor hypoxia, the emergence of drug resistance, and glutaminolysis-induced metabolic reprogramming and presenting metabolic strategies to target glutamine metabolism in cancer cells. In this review, we introduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
441
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 568 publications
(454 citation statements)
references
References 206 publications
9
441
0
4
Order By: Relevance
“…The few that were detected were present at relatively low levels compared with those present in other amino acid-degradative processes such as glutaminolysis. This may be related to the reduced accessibility of these alternatives in culture medium and their less preferential metabolic utilisation compared with glutamine [64]. Of those that were detected, the expression of two was significantly altered in ME/CFS lymphoblast proteomes.…”
Section: Expression Of Enzymes Involved In the Mitochondrial Utilisatmentioning
confidence: 99%
“…The few that were detected were present at relatively low levels compared with those present in other amino acid-degradative processes such as glutaminolysis. This may be related to the reduced accessibility of these alternatives in culture medium and their less preferential metabolic utilisation compared with glutamine [64]. Of those that were detected, the expression of two was significantly altered in ME/CFS lymphoblast proteomes.…”
Section: Expression Of Enzymes Involved In the Mitochondrial Utilisatmentioning
confidence: 99%
“…In the current research, we verified that miR-330-3p directly bound to GLS 3'-UTR and negatively regulated GLS expression. Aberrant energy metabolism, such as increased glutamine catabolism, is one of critical hallmarks of cancer (33,34). In addition to abnormal glycolysis, several previous studies revealed that enhanced glutamine metabolism was correlated with tumor metastasis and poor prognosis in patients with cancer (12,35).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is both a cellular building block and an indirect fuel for the TCA cycle 38, 39 and was described as the primary energy fuel for HeLa cells 40 . Depending on the cellular metabolic state, glutamine can be used as either a biosynthetic precursor for proteins, nucleotides or glutathione, or as an anaplerotic fuel that drives mitochondrial ATP production 41, 42 . Without its presence in glucose-free culture medium, it is difficult to predict the adaptations in energy metabolism of NHDF cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate can be converted into acetyl-CoA and enter the TCA cycle, thus being an energy source for cells 46 . However, if pyruvate is the only source of energy, this will probably only work in short-term because there would be no source to maintain the pool of TCA cycle intermediates that are used in other metabolic pathways, as opposed to what happens when glutamine is the main fuel 41 . Pyruvate supplementation in culture media without glucose is not entirely consensual.…”
Section: Discussionmentioning
confidence: 99%